Cooperative capitalism - Schaed, Ulrike (Oxford University Press, 2000)
The Japanese government is becoming less involved in shaping industrial policy--but what does this imply for the openness of Japanese markets to foreign competition? In an extensive study of 'post-development' Japan, Ulrike Schaede argues that, contrary to what many have suggested, the reduced role of government regulation may not result in more open markets. Instead, as has happened throughout Japanese history, deregulation and the recession of the 1990s have once again led Japanese trade associations to assume important regulatory functions of their own